An investigation into the key considerations which impact decisions to undertake IT Outsourcing in the UK Banking Industry. - Premji, Sachin (2014)
Purpose – The purpose of this dissertation is to investigate the key considerations which impact decisions to undertake IT Outsourcing in a UK banking context.